Dark Side of the Moon: Jameson, David Foster Wallace and the Critique of Neoliberalism in Brief Interviews with Hideous Men - Golbarg Darvishian; Javad Yaghoobi Derabi (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
The purpose of the present research is to read Brief Interviews with Hideous Men in the light of Fredric Jameson's theories. In Brief Interviews with Hideous Men, the writer depicts how irony and self-consciousness have penetrated the culture of postmodern man and how capitalism and neoliberalism have influenced people's lives and identities and, with the help of ideology, have turned man into a thing incapable of human relations. Fredric Jameson declares that historicizing literary texts can help the readers understand the latent and deep layers of meaning in the works. Jameson's main concern is that in a neoliberal society, the authorities use ideology to preserve power, and by ideology, they turn citizens into consumers. The result is the alienation and reification of people, and they lose their true identities, which is the death of the postmodern man. By reading this short story collection from a Jamesonian perspective, the reader tries to investigate the man's identity in a neoliberal society to show how a closed system like a neoliberal system can preserve power by using ideology to influence the mindset of the citizens and reify and alienate them and impose the superiority of market on them. This research shows how Wallace investigates man’s identity in a neoliberal society to show how a closed system like a neoliberal system can preserve power by using ideology to influence the mindset of the citizens and reify and alienate them and impose the superiority of market on them and how the identity of people is gone and how the death of the postmodern man has happened.